Eksperimen Rumah Pengering Ikan Sarden Model Ultra Violet (UV) Solar Dryer Kombinasi dengan Sistem Solar Air Heater Melalui Variasi Kecepatan Udara Keluar - Punuf, Rolandi; Riwu, Defmit B.N.; Koehuan, Verdy A. (Universitas Nusa Cendana, 2023)
The technique for preserving a new product is by using a drying technique. The development and utilization of solar energy must continue to be developed with several technologies including the Solar Air Heater. The research method used was an experimental method on Ultra-Violet solar dryer drying houses for drying sardines with additional absorption of solar radiation heat using a solar air heater system. This configuration works by drawing air from the building envelope or from the outside environment and passing it through a collector where the air is warmed by conduction and convection in the absorber. The analysis of this study is regarding the velocity of the airflow coming out of the drying chamber, namely 1.0 m/s, 1.5 m/s and 1.8 m/s, while the airflow velocity in the solar panel (exhaust fan) is 3.5 m/s (constant). The results of the study show that the addition of heat through the solar air heater panel can speed up the drying process in the drying chamber. The temperature difference in the solar panel increases the heat absorbed through the hot air flow which also increases the efficiency of the solar panel. The highest efficiency of the drying house is 48.05 % occurring at the outlet air flow rate of 1.8 m/s. The temperature difference in the drying chamber and the increased ambient air tends to increase the efficiency of the drying chamber where in this study the highest value of 48.05% was obtained at a speed of 1.8 m/s